2011
DOI: 10.1104/pp.111.180067
|View full text |Cite
|
Sign up to set email alerts
|

Interfamily Transfer of TomatoVe1MediatesVerticilliumResistance in Arabidopsis      

Abstract: Vascular wilts caused by soil-borne fungal species of the Verticillium genus are devastating plant diseases. The most common species, Verticillium dahliae and Verticillium albo-atrum, have broad host ranges and are notoriously difficult to control. Therefore, genetic resistance is the preferred method for disease control. Only from tomato (Solanum lycopersicum) has a Verticillium resistance locus been cloned, comprising the Ve1 gene that encodes a receptor-like protein-type cell surface receptor. Due to lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
252
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(261 citation statements)
references
References 77 publications
4
252
1
4
Order By: Relevance
“…Several lines of evidence have suggested that JA signaling is also required for plant resistance to V. dahliae, as revealed by the exogenous application of MeJA (Fig. 2, A and B) and by genetic and molecular biology analyses in Arabidopsis and cotton (Fradin et al, 2011;Gao et al, 2013). Furthermore, GbWRKY1 showed clear negative regulation in JA-mediated defense gene expression and anthocyanin accumulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have suggested that JA signaling is also required for plant resistance to V. dahliae, as revealed by the exogenous application of MeJA (Fig. 2, A and B) and by genetic and molecular biology analyses in Arabidopsis and cotton (Fradin et al, 2011;Gao et al, 2013). Furthermore, GbWRKY1 showed clear negative regulation in JA-mediated defense gene expression and anthocyanin accumulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Verticillium wilt Ve1-mediated resistance is compromised in the Arabidopsis JA response mutant jar1-1 (Fradin et al, 2011), and the JA signaling pathway can be activated in cotton by inoculation with V. dahliae , suggesting that JA plays an important role in cotton resistance to V. dahliae. To further evaluate the role of JA in cotton's defense against V. dahliae, cotton seedlings were treated with methyl jasmonate (MeJA) 2 d before inoculation with V. dahliae.…”
Section: Gbwrky1 Negatively Regulates the Ja Signaling Pathwaymentioning
confidence: 99%
“…A small number of RLPs, such as the tomato (Solanum lycopersicum) Cf and Ve proteins and the apple (Malus domestica) HcrVf2 protein, were shown to function as R proteins (Jones et al, 1994;Kawchuk et al, 2001;Belfanti et al, 2004;Fradin et al, 2009). Interestingly, Ve1-mediated resistance to Verticillium requires BAK1 (Fradin et al, 2009(Fradin et al, , 2011. Two other RLPs, tomato Eix1 and Eix2, function as receptors for the fungal ethylene-inducing xylanase (Ron and Avni, 2004).…”
mentioning
confidence: 99%
“…4 In addition, it has been found that RLPs are important players in disease resistance. The RLP disease resistance genes include the tomato Cf and Ve genes that provide resistance against Cladosporium fulvum and Verticillium spp., respectively, 5,6 LeEIX genes that combat against the ethylene-inducing xylanase produced from Trichoderma biocontrol fungi, 7 apple HcrVf genes that confer resistance to the scab fungus Venturia inaequalis, 8 the LepR3 and Rlm2 genes that render race-specific resistance to the fungal pathogen Leptosphaeria maculans. 9,10 Genome-wide sequence analyses identified a total of 57 AtRLPs in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…1 Nevertheless, the generation of gain-of-function mutants has produced invaluable information on the function of AtRLP genes such as TMM, Ve1, AtRLP23 and AtRLP44. 6,15,17,21 We thus performed a genome-wide functional analysis of AtRLP genes using overexpression analysis to gain additional insights into their potential roles in various aspects such as Arabidopsis growth and development, and salt tolerance. 20 Despite the absence of any phenotypic alterations under normal growth condition, the overexpression of AtRLP3 and AtRLP11 could rescue the clv2-1 mutant.…”
Section: Introductionmentioning
confidence: 99%